Effects of Lactobacillus plantarum FZU3013-Fermented Laminaria japonica on Lipid Metabolism and Gut Microbiota in Hyperlipidaemic Rats - Hu, Jin-Peng; Zheng, Ting-Ting; Zeng, Bin-Fen; Wu, Man-Ling; Shi, Rui; Zhang, Ye; Chen, Li-Jiao; Cheng, Wen-Jian; Liang, Peng (Frontiers in Nutrition, 2021)
In this study, we explored the effect of Lactobacillus plantarum FZU3013-fermented Laminaria japonica (LPLJ) supplementation to prevent hyperlipidaemia in rats fed with a high-fat diet (HFD). The results indicate that LPLJ supplementation improved serum and hepatic biochemical indicators (p < 0.05), elevated short-chain fatty acid levels, reduced the accumulation of lipid droplets in the liver that are caused by an HFD, modulated the relative abundance of some microbial phylotypes, and reduced hyperlipidaemia in HFD-fed rats by adjusting the aminoacyl-tRNA, phenylalanine, tyrosine, and tryptophan biosynthetic pathways, as well as the phenylalanine, D-glutamine and D-glutamate, and glutathione metabolic pathways. Additionally, hepatic mRNA levels of the genes involved in lipid metabolism and bile acid homeostasis were significantly reduced by LPLJ intervention (p < 0.05). These results suggest that LPLJ has a positive effect on modulating lipid metabolism and has the potential to be a functional food that can help prevent hyperlipidaemia.